2005
DOI: 10.1002/pbc.20205
|View full text |Cite
|
Sign up to set email alerts
|

Use of alternative and complementary therapies in children with cancer

Abstract: CAM is likely to be used by a wide variety of people. In our study, we found that about half of the children with cancer has used CAM in the 2 preceding months. No specific profile of CAM users emerged from this study. The high prevalence of CAM warrants further studies to better understand the reasons and consequences of CAM use particularly on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
5
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 27 publications
7
87
5
17
Order By: Relevance
“…Cultural differences may play an important role in the use of CAM. Martel et al [6] reported that about half of pediatric oncology Quebec population uses at least one type of CAM. Our results are consistent with the finding of more recent studies in pediatric cancer patients that reported a prevalence of 84%, 73%, and 70% on CAM use, in United States, Taiwan, and Mexico respectively [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural differences may play an important role in the use of CAM. Martel et al [6] reported that about half of pediatric oncology Quebec population uses at least one type of CAM. Our results are consistent with the finding of more recent studies in pediatric cancer patients that reported a prevalence of 84%, 73%, and 70% on CAM use, in United States, Taiwan, and Mexico respectively [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of the contents of the articles reviewed, four thematic categories emerged: quality of life and the elements of spirituality (8,14,(19)(20) ; alternative and complementary therapies: spirituality as a therapeutic resource (6,9,13,16,23,25) ; spirituality as a coping strategy (5,7,11,17,18,22,24) and spirituality as an attribute of the existential transformations (10,12,15,21) . Use of alternative therapies for children with cancer (6) Friedman et al…”
Section: Resultsmentioning
confidence: 99%
“…Spirituality acts as a positive factor for compatibility of child and her family with cancer (40). So that spiritual distress is a cause for anxiety and maladaptive behaviors (41). Since the role of religion is so important in Iranian culture, and several studies indicate high incidence of religious and spiritual challenges in cancer patients or their families (17,42,43), familiarity of nurses with this nursing diagnosis and necessary interventions to change the spiritual insight of mothers of children with cancer is essential.…”
Section: Discussionmentioning
confidence: 99%